30-14x=-5(6x+4)-5(-8-3x)

Simple and best practice solution for 30-14x=-5(6x+4)-5(-8-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30-14x=-5(6x+4)-5(-8-3x) equation:


Simplifying
30 + -14x = -5(6x + 4) + -5(-8 + -3x)

Reorder the terms:
30 + -14x = -5(4 + 6x) + -5(-8 + -3x)
30 + -14x = (4 * -5 + 6x * -5) + -5(-8 + -3x)
30 + -14x = (-20 + -30x) + -5(-8 + -3x)
30 + -14x = -20 + -30x + (-8 * -5 + -3x * -5)
30 + -14x = -20 + -30x + (40 + 15x)

Reorder the terms:
30 + -14x = -20 + 40 + -30x + 15x

Combine like terms: -20 + 40 = 20
30 + -14x = 20 + -30x + 15x

Combine like terms: -30x + 15x = -15x
30 + -14x = 20 + -15x

Solving
30 + -14x = 20 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
30 + -14x + 15x = 20 + -15x + 15x

Combine like terms: -14x + 15x = 1x
30 + 1x = 20 + -15x + 15x

Combine like terms: -15x + 15x = 0
30 + 1x = 20 + 0
30 + 1x = 20

Add '-30' to each side of the equation.
30 + -30 + 1x = 20 + -30

Combine like terms: 30 + -30 = 0
0 + 1x = 20 + -30
1x = 20 + -30

Combine like terms: 20 + -30 = -10
1x = -10

Divide each side by '1'.
x = -10

Simplifying
x = -10

See similar equations:

| 8(3+w)=7(2+w) | | 0=3042+x^2-117x | | 7+8y-12=3y-8y+5y | | X^3+6x^2+12x=0 | | P=3042+x^2-117x | | 9=6 | | 5.6X-17.2+2.4X=5.2+9x | | k/8=0 | | 15+2h=3x-15 | | 7x-1=61 | | 13-5X=5X+9-9X | | -10=14 | | 3(2x+4)=-2+6x+14 | | 26-2x=9-6x | | 6x-7x-3=-21 | | 1r+40=50 | | (e^(9x))/(x-6) | | -6X+9+7X=14-25 | | -x=18x+x | | 76+104+104+10x-4=360 | | 90+90+15x+16x-6=360 | | 6q+3x=4x+11 | | 5300=x(2650-x) | | x+3=2x+16 | | P^2-8p-20=0 | | (7+z)(4z-9)=0 | | 2(x+4)=x-5y | | 70+4=7 | | 66+74+110+17x+8=360 | | 8z=4Z-3+3Z | | 5(x-3)+6=5x | | 500=120+12n |

Equations solver categories